Zadłużenie gospodarstw domowych a dynamika wydatków konsumpcyjnych w krajach OECD po wybuchu kryzysu finansowego - Bolibok, Piotr (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
The paper aims at empirical evaluation of the impact of household debt on the dynamics of consumption spending since the beginning of the global financial crisis. The research employed linear regression analysis of the rate of growth of household spending against the rate of growth of disposable income, the level of indebtedness and long-term interest rates in the OECD member states between 2008-2014. The results obtained indicate that household indebtedness was one of the factors influencing the dynamics of consumption demand and thus the processes of economic growth in the OECD states after the beginning of the global financial crisis. Variations in the relation of total debt to net disposable income and in the level of long-term interest rates were both negatively related to the changes in consumption spending. This impact turned out to be markedly stronger when total household debt of a given country was exceeding 85% of GDP, which is consistent with the results of previous investigations on the in&uence of the indebtedness of household sector on the dynamics of economic growth